Strategi Perencanaan dan Pelaksanaan Program Humas dalam Mendukung Pengembangan Madrasah Aliyah Nurul Islam Jember - Ahmad Aril Athok Illah; Afina Afanin Nabila; Ardita Dwi Subakti; Ahmad Sholeh; Rofiq Hidayat (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
School-Owned Enterprises (BUMES) and the public relations division of the madrasah play a strategic role in supporting institutional development through systematic and sustainable program planning and implementation. BUMES functions not only as the school’s entrepreneurship unit but also as a bridge for collaboration with external institutions, including universities, government agencies, and international partners. During specific periods, particularly toward the end of the academic year, the intensity of cooperation increases, marked by the execution of several strategic programs. In addition to routine activities such as internships at BBDB, BUMES and the public relations division also initiate innovative programs, including a student exchange program to Thailand. This initiative aims to expand global networking, strengthen student competitiveness, and provide cross-cultural learning experiences. All programs are designed through organized planning processes from the beginning of the semester, taking into account relevance, sustainability, and implementation efficiency. This ensures that each activity aligns with the vision and needs of the madrasah while maximizing benefits for students and the institution. The implementation of these programs demonstrates that the synergy between BUMES and the public relations division significantly enhances educational service quality, strengthens institutional image, and supports comprehensive improvement in school performance.